A kind of antifreeze type ultra-high performance concrete early strength agent and its preparation method and application

By using polypropylene, maleic anhydride grafted polypropylene, sodium chloride and silica sol in concrete to form an efficient fiber structure and dense network, the problem of frozen cracks and insufficient strength in concrete in high-altitude areas is solved, and the resistance to freezing is significantly improved and impermeability, extending the service life of the building.

CN118724503BActive Publication Date: 2024-12-27INST OF ROCK & SOIL MECHANICS CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410926573.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-11
Publication Date
2024-12-27
Estimated Expiration
2044-07-11

AI Technical Summary

Technical Problem

Existing concrete early strength agents cannot effectively solve the problems of frozen cracks, decanted and swelling cracks in low-temperature environments in high-altitude areas, and the strength growth is slow, affecting the service life of the building.

Method used

Polypropylene and maleic anhydride grafted polypropylene and sodium chloride as core layer raw materials, polyethylene, sodium polyacrylate and aluminum trichloride as cortical raw materials, combined with silica sol and methyl orthosilicate to form an efficient fiber structure and dense three-dimensional network structure to enhance the compressive strength and permeability of concrete.

Benefits of technology

It significantly improves the frost resistance and permeability of concrete at low temperatures, shortens the production cycle, extends the service life of the building, and improves the production efficiency of concrete in high-altitude areas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118724503B_ABST
    Figure CN118724503B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of concrete early strength agent, and specifically discloses an antifreeze type ultra-high performance concrete early strength agent, wherein the raw materials include by mass: 10-15 parts of polypropylene, 1-2 parts of maleic anhydride grafted polypropylene, 1-4 parts of sodium chloride, 5-10 parts of polyethylene, 1-2 parts of sodium polyacrylate, 1-2 parts of aluminum chloride, 4-10 parts of diethanolamine, 1-6 parts of triisopropanolamine, 1-2 parts of sodium sulfate, 1-2 parts of silica sol, 1-2 parts of methyl orthosilicate, 1-2 parts of calcium formate, 1-2 parts of aluminum sulfate, 10-20 parts of composite water reducer, and 0.1-1 parts of defoamer. The present invention also discloses a preparation method of the above-mentioned antifreeze type ultra-high performance concrete early strength agent. The present invention also discloses the application of the above-mentioned antifreeze type ultra-high performance concrete early strength agent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete early strength agents, and in particular to an antifreeze type ultra-high performance concrete early strength agent and a preparation method and application thereof. Background Art

[0002] With the large-scale application of concrete materials in construction projects, concrete, as a non-homogeneous porous material, has a large number of microstructural defects inside, and these defects will become the permeation channels of ions, liquids and gases in the later stage under certain conditions. At the same time, due to the shrinkage and hydration properties of cement-based materials themselves, the risk of shrinkage cracking and low-temperature freezing cracking is very likely to occur, which brings new technical challenges to the application of concrete in safe and high-quality projects in high-altitude cold regions.

[0003] At present, concrete production and application are affected by the low temperature and lack of oxygen in high-altitude and cold areas, resulting in low concrete production efficiency, insufficient hydration heat, insufficient strength, and insufficient frost resistance, which in turn causes weathering, voiding, and cracking. The slow growth of concrete strength is the main problem, which directly affects the service life of buildings.

[0004] Concrete early strength agent is a substance added before or during the mixing process to improve the performance of concrete. It is an indispensable material in concrete. Commonly used early strength agents have a single function and cannot solve the problems of concrete cracking and leakage and poor frost resistance at the same time. They cannot adapt to the complex environment of the plateau. Summary of the invention

[0005] The purpose of the present invention is to solve the shortcomings of the prior art and to propose an antifreeze type ultra-high performance concrete early strength agent and a preparation method and application thereof.

[0006] The invention discloses an antifreeze type ultra-high performance concrete early strength agent. The raw materials thereof include, by mass, 10-15 parts of polypropylene, 1-2 parts of maleic anhydride grafted polypropylene, 1-4 parts of sodium chloride, 5-10 parts of polyethylene, 1-2 parts of sodium polyacrylate, 1-2 parts of aluminum chloride, 4-10 parts of diethanolamine, 1-6 parts of triisopropanolamine, 1-2 parts of sodium sulfate, 1-2 parts of silica sol, 1-2 parts of methyl orthosilicate, 1-2 parts of calcium formate, 1-2 parts of aluminum sulfate, 10-20 parts of composite water reducing agent and 0.1-1 part of defoaming agent.

[0007] Preferably, the composite water reducer comprises: polycarboxylic acid high-efficiency water reducer and sodium gluconate.

[0008] Preferably, the mass ratio of polycarboxylate high-efficiency water reducer to sodium gluconate is 9-18:1-2.

[0009] Preferably, the defoaming agent is a silicone defoaming agent.

[0010] The preparation method of the above-mentioned antifreeze type ultra-high performance concrete early strength agent comprises the following steps:

[0011] S1, mixing polypropylene, maleic anhydride grafted polypropylene and sodium chloride uniformly, and melting them to obtain a molten material α;

[0012] S2, mixing polyethylene, sodium polyacrylate and aluminum chloride uniformly, and melting them to obtain a molten material β;

[0013] S3, using the molten material α as the core material and the molten material β as the skin material and feeding them into a composite spinning machine, spraying them out from a spinneret, cooling, cutting, soaking, ultrasonically washing, vacuum drying, adding diethanolamine, triisopropanolamine, sodium sulfate, and anhydrous ethanol for ultrasonic dispersion for 1-2h, removing the anhydrous ethanol, and crushing to obtain an early strength prefabricated material a;

[0014] S4, adding silica sol and methyl orthosilicate to anhydrous ethanol and stirring for 1-2h, adding ammonia solution thereto under stirring to adjust the system to be neutral, continuing stirring for 1-2h, adding calcium formate and aluminum sulfate and stirring for 5-15min, standing for 5-10h, and vacuum drying to obtain early strength prefabricated material b;

[0015] S5. Evenly mix the composite water reducing agent, early strength prefabricated material a and early strength prefabricated material b, add the defoaming agent and stir evenly, stir and dry, cool to room temperature, and crush.

[0016] Preferably, in S3, after cutting, the pieces are immersed in anhydrous ethanol and water in sequence.

[0017] Preferably, in S3, the frequency of ultrasonic dispersion is 5-12 kHz.

[0018] Preferably, in S4, the mass fraction of the aqueous ammonia solution is 20-26%.

[0019] Preferably, in S5, the stirring and drying temperature is 100-120°C.

[0020] The above-mentioned antifreeze type ultra-high performance concrete early strength agent is used in an amount of 0.5-0.8% of the cementitious material in the concrete.

[0021] Beneficial effects:

[0022] The invention adopts polypropylene, maleic anhydride grafted polypropylene and sodium chloride as core layer raw materials, polyethylene, sodium polyacrylate and aluminum chloride as skin layer raw materials, the core layer and the skin layer have high bonding strength under the action of maleic anhydride grafted polypropylene, and after ultrasonic washing with anhydrous ethanol and water, the aluminum chloride in the skin layer can be fully washed, and the formed through-hole structure can promote the sodium chloride in the core layer to be further washed and escaped, so that the obtained fiber structure has high adsorption strength for diethanolamine, triisopropanolamine and calcium formate, and the sodium polyacrylate in the skin layer absorbs water and expands to provide expansion space, and the pore structure in the core layer can keep the internal water content constant, ensure the continuous progress of cement hydration, improve the microstructure of hydration products, improve the compressive strength of concrete, and further reduce the shrinkage rate and shorten the production cycle, and cooperate with the precipitation of diethanolamine, triisopropanolamine and sodium sulfate to promote the concrete to be more dense, and effectively improve the impermeability and frost resistance of concrete.

[0023] Silica sol is compounded with tetraethyl orthosilicate, and calcium formate and aluminum sulfate are combined in the formed silica aerogel structure to form a dense three-dimensional network structure in the concrete. This not only promotes the bonding of internal particles, making the cementitious material denser, and the interfacial bonding stronger, but also further enhances the anti-seepage and anti-freeze-thaw effects. At the same time, because the new three-dimensional structure with nano-silica as the node is compounded on the basis of the original network structure of the concrete, it greatly reduces defects such as cracks, prolongs the service life and improves safety.

[0024] The present invention can accelerate the hydration effect, control the setting time of concrete, improve the early mechanical properties, enhance the impermeability and frost resistance, and improve the durability while increasing the water reduction effect.

[0025] The high-altitude cold region concrete strengthener developed by the present invention aims at the problems of freeze cracking, voiding and expansion cracking that are prone to occur in high-altitude cold region concrete. The concrete strengthener not only promotes the rapid early hydration of cement, but also the organic and inorganic substances work together to promote the hydration of cement at low temperature, thereby rapidly improving the strength of concrete, improving the concrete production efficiency, improving the development of the strength of concrete at low temperature, and ensuring the quality of concrete. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The figure is a comparison chart of the air content of concrete prepared by using the early strength agent obtained in Example 5 and Comparative Examples 1-2.

[0027] Figure 2 The figure is a comparison chart of the slump and expansion of concrete prepared by using the early strength agent obtained in Example 5 and Comparative Examples 1-2.

[0028] Figure 3 The following is a comparison chart of the compressive strength of concrete prepared using the early strength agent obtained in Example 5 and Comparative Examples 1-2 at different curing times.

[0029] Figure 4The figure is a comparison chart of the strength loss rate of concrete made by using the early strength agent obtained in Example 5 and Comparative Examples 1-2 and after being cured for 28 days and subjected to 100 freeze-thaw cycles. DETAILED DESCRIPTION

[0030] The present invention will be further explained below in conjunction with specific embodiments.

[0031] Example 1

[0032] An antifreeze type ultra-high performance concrete early strength agent, whose raw materials include: 1000g of polypropylene, 100g of maleic anhydride grafted polypropylene, 100g of sodium chloride, 500g of polyethylene, 100g of sodium polyacrylate, 100g of aluminum chloride, 400g of diethanolamine, 100g of triisopropanolamine, 100g of sodium sulfate, 100g of silica sol, 100g of methyl orthosilicate, 100g of calcium formate, 100g of aluminum sulfate, 1000g of composite water reducing agent, and 10g of silicone defoaming agent.

[0033] The composite water reducer is composed of polycarboxylic acid high-efficiency water reducer and sodium gluconate in a mass ratio of 9:1.

[0034] The preparation method of the above-mentioned antifreeze type ultra-high performance concrete early strength agent comprises the following steps:

[0035] S1, mixing polypropylene, maleic anhydride grafted polypropylene and sodium chloride uniformly, and melting them to obtain a molten material α;

[0036] S2, mixing polyethylene, sodium polyacrylate and aluminum chloride uniformly, and melting them to obtain a molten material β;

[0037] S3, using the molten material α as the core material and the molten material β as the skin material and feeding them into a composite spinning machine, spraying them out from a spinneret, cooling, cutting, soaking them in anhydrous ethanol and water in turn, ultrasonically washing them, vacuum drying, adding diethanolamine, triisopropanolamine, sodium sulfate, and 5000g of anhydrous ethanol for ultrasonic dispersion for 1h, with an ultrasonic frequency of 5kHz, removing anhydrous ethanol, and crushing to obtain an early strength prefabricated material a;

[0038] S4, adding silica sol and methyl orthosilicate to 500g of anhydrous ethanol and stirring for 1h, adding 20% ​​by mass ammonia solution thereto under stirring, adjusting the system to be neutral, continuing stirring for 1h, adding calcium formate and aluminum sulfate and stirring for 5min, standing for 5h, and vacuum drying to obtain early strength prefabricated material b;

[0039] S5. Evenly mix the composite water reducing agent, early strength prefabricated material a and early strength prefabricated material b, add the organosilicon defoaming agent and stir evenly, stir and dry at 100°C with a stirring speed of 10r / min, cool to room temperature and crush.

[0040] Example 2

[0041] An antifreeze type ultra-high performance concrete early strength agent, whose raw materials include: 1500g of polypropylene, 200g of maleic anhydride grafted polypropylene, 400g of sodium chloride, 1000g of polyethylene, 200g of sodium polyacrylate, 200g of aluminum chloride, 1000g of diethanolamine, 600g of triisopropanolamine, 200g of sodium sulfate, 200g of silica sol, 200g of methyl orthosilicate, 200g of calcium formate, 200g of aluminum sulfate, 2000g of composite water reducing agent, and 100g of silicone defoaming agent.

[0042] The composite water reducer is composed of polycarboxylic acid high-efficiency water reducer and sodium gluconate in a mass ratio of 18:2.

[0043] The preparation method of the above-mentioned antifreeze type ultra-high performance concrete early strength agent comprises the following steps:

[0044] S1, mixing polypropylene, maleic anhydride grafted polypropylene and sodium chloride uniformly, and melting them to obtain a molten material α;

[0045] S2, mixing polyethylene, sodium polyacrylate and aluminum chloride uniformly, and melting them to obtain a molten material β;

[0046] S3, using the molten material α as the core material and the molten material β as the skin material and feeding them into a composite spinning machine, spraying them out from a spinneret, cooling, cutting, soaking them in anhydrous ethanol and water in turn, ultrasonically washing them, vacuum drying, adding diethanolamine, triisopropanolamine, sodium sulfate, and 10000g of anhydrous ethanol for ultrasonic dispersion for 2h, with an ultrasonic frequency of 12kHz, removing anhydrous ethanol, and crushing to obtain an early strength prefabricated material a;

[0047] S4, adding silica sol and methyl orthosilicate to 1500g of anhydrous ethanol and stirring for 2h, adding 26% ammonia solution under stirring to adjust the system to be neutral, continuing stirring for 2h, adding calcium formate and aluminum sulfate and stirring for 15min, standing for 10h, and vacuum drying to obtain early strength prefabricated material b;

[0048] S5. Evenly mix the composite water reducing agent, early strength prefabricated material a and early strength prefabricated material b, add the organosilicon defoamer and stir evenly, stir and dry at 120°C with a stirring speed of 50r / min, cool to room temperature and crush.

[0049] Example 3

[0050] An antifreeze type ultra-high performance concrete early strength agent, whose raw materials include: 1100g of polypropylene, 180g of maleic anhydride grafted polypropylene, 200g of sodium chloride, 900g of polyethylene, 130g of sodium polyacrylate, 180g of aluminum chloride, 600g of diethanolamine, 400g of triisopropanolamine, 130g of sodium sulfate, 180g of silica sol, 130g of methyl orthosilicate, 180g of calcium formate, 130g of aluminum sulfate, 1800g of composite water reducing agent, and 30g of silicone defoaming agent.

[0051] The composite water reducer is composed of polycarboxylic acid high-efficiency water reducer and sodium gluconate in a mass ratio of 18:1.

[0052] The preparation method of the above-mentioned antifreeze type ultra-high performance concrete early strength agent comprises the following steps:

[0053] S1, mixing polypropylene, maleic anhydride grafted polypropylene and sodium chloride uniformly, and melting them to obtain a molten material α;

[0054] S2, mixing polyethylene, sodium polyacrylate and aluminum chloride uniformly, and melting them to obtain a molten material β;

[0055] S3, using the molten material α as the core material and the molten material β as the skin material and feeding them into a composite spinning machine, spraying them out from a spinneret, cooling, cutting, soaking them in anhydrous ethanol and water in turn, ultrasonically washing them, vacuum drying, adding diethanolamine, triisopropanolamine, sodium sulfate, and 9000g of anhydrous ethanol for ultrasonic dispersion for 80min, with an ultrasonic frequency of 9kHz, removing anhydrous ethanol, and crushing to obtain an early strength prefabricated material a;

[0056] S4, adding silica sol and methyl orthosilicate to 800g of anhydrous ethanol and stirring for 100min, adding 22% by mass ammonia solution thereto under stirring, adjusting the system to be neutral, continuing stirring for 100min, adding calcium formate and aluminum sulfate and stirring for 8min, standing for 8h, and vacuum drying to obtain early strength prefabricated material b;

[0057] S5. Evenly mix the composite water reducing agent, early strength prefabricated material a and early strength prefabricated material b, add the organosilicon defoaming agent and stir evenly, stir and dry at a temperature of 105°C and a stirring speed of 40r / min, cool to room temperature, and crush.

[0058] Example 4

[0059] A freeze-proof ultra-high performance concrete early strength agent, whose raw materials include: 1300g of polypropylene, 120g of maleic anhydride grafted polypropylene, 300g of sodium chloride, 700g of polyethylene, 170g of sodium polyacrylate, 120g of aluminum chloride, 800g of diethanolamine, 200g of triisopropanolamine, 170g of sodium sulfate, 120g of silica sol, 170g of methyl orthosilicate, 120g of calcium formate, 170g of aluminum sulfate, 1200g of composite water reducing agent, and 70g of silicone defoaming agent.

[0060] The composite water reducer is composed of polycarboxylic acid high-efficiency water reducer and sodium gluconate in a mass ratio of 9:2.

[0061] The preparation method of the above-mentioned antifreeze type ultra-high performance concrete early strength agent comprises the following steps:

[0062] S1, mixing polypropylene, maleic anhydride grafted polypropylene and sodium chloride uniformly, and melting them to obtain a molten material α;

[0063] S2, mixing polyethylene, sodium polyacrylate and aluminum chloride uniformly, and melting them to obtain a molten material β;

[0064] S3, using the molten material α as the core material and the molten material β as the skin material and feeding them into a composite spinning machine, spraying them out from a spinneret, cooling, cutting, soaking them in anhydrous ethanol and water in turn, ultrasonically washing them, vacuum drying, adding diethanolamine, triisopropanolamine, sodium sulfate, and 7000g of anhydrous ethanol for ultrasonic dispersion for 100min, with an ultrasonic frequency of 6kHz, removing anhydrous ethanol, and crushing them to obtain an early strength prefabricated material a;

[0065] S4, adding silica sol and methyl orthosilicate to 1200g of anhydrous ethanol and stirring for 80min, adding 24% ammonia solution under stirring to adjust the system to be neutral, continuing stirring for 80min, adding calcium formate and aluminum sulfate and stirring for 12min, standing for 6h, and vacuum drying to obtain early strength prefabricated material b;

[0066] S5. Evenly mix the composite water reducing agent, early strength prefabricated material a and early strength prefabricated material b, add the organosilicon defoaming agent and stir evenly, stir and dry at a temperature of 115°C with a stirring speed of 20r / min, cool to room temperature, and crush.

[0067] Example 5

[0068] An antifreeze type ultra-high performance concrete early strength agent, whose raw materials include: 1200g of polypropylene, 150g of maleic anhydride grafted polypropylene, 250g of sodium chloride, 800g of polyethylene, 150g of sodium polyacrylate, 150g of aluminum chloride, 700g of diethanolamine, 300g of triisopropanolamine, 150g of sodium sulfate, 150g of silica sol, 150g of methyl orthosilicate, 150g of calcium formate, 150g of aluminum sulfate, 1500g of composite water reducing agent, and 50g of silicone defoaming agent.

[0069] The composite water reducer is composed of polycarboxylic acid high-efficiency water reducer and sodium gluconate in a mass ratio of 9:1.

[0070] The preparation method of the above-mentioned antifreeze type ultra-high performance concrete early strength agent comprises the following steps:

[0071] S1, mixing polypropylene, maleic anhydride grafted polypropylene and sodium chloride uniformly, and melting them to obtain a molten material α;

[0072] S2, mixing polyethylene, sodium polyacrylate and aluminum chloride uniformly, and melting them to obtain a molten material β;

[0073] S3, using the molten material α as the core material and the molten material β as the skin material and feeding them into a composite spinning machine, spraying them out from a spinneret, cooling, cutting, soaking them in anhydrous ethanol and water in turn, ultrasonically washing them, vacuum drying, adding diethanolamine, triisopropanolamine, sodium sulfate, and 8000g of anhydrous ethanol for ultrasonic dispersion for 90 minutes, with an ultrasonic frequency of 7.5kHz, removing anhydrous ethanol, and crushing to obtain an early strength prefabricated material a;

[0074] S4, adding silica sol and methyl orthosilicate to 1000g of anhydrous ethanol and stirring for 90min, adding 23% by mass ammonia solution thereto under stirring, adjusting the system to be neutral, continuing stirring for 90min, adding calcium formate and aluminum sulfate and stirring for 10min, standing for 7h, and vacuum drying to obtain early strength prefabricated material b;

[0075] S5. Evenly mix the composite water reducing agent, early strength prefabricated material a and early strength prefabricated material b, add the organosilicon defoaming agent and stir evenly, stir and dry at a temperature of 110°C at a stirring speed of 30r / min, cool to room temperature, and crush.

[0076] Comparative Example 1

[0077] A super high performance concrete early strength agent, whose raw materials include: 1200g of polypropylene, 150g of maleic anhydride grafted polypropylene, 800g of polyethylene, 150g of sodium polyacrylate, 150g of aluminum chloride, 700g of diethanolamine, 300g of triisopropanolamine, 150g of sodium sulfate, 150g of silica sol, 150g of methyl orthosilicate, 150g of calcium formate, 150g of aluminum sulfate, 1500g of composite water reducing agent, and 50g of silicone defoaming agent.

[0078] The composite water reducer is composed of polycarboxylic acid high-efficiency water reducer and sodium gluconate in a mass ratio of 9:1.

[0079] The preparation method of the ultra-high performance concrete early strength agent comprises the following steps:

[0080] S1, mixing polypropylene and maleic anhydride grafted polypropylene uniformly, and melting them to obtain a molten material α;

[0081] S2, mixing polyethylene, sodium polyacrylate and aluminum chloride uniformly, and melting them to obtain a molten material β;

[0082] S3, using the molten material α as the core material and the molten material β as the skin material and feeding them into a composite spinning machine, spraying them out from a spinneret, cooling, cutting, soaking them in anhydrous ethanol and water in turn, ultrasonically washing them, vacuum drying, adding diethanolamine, triisopropanolamine, sodium sulfate, and 8000g of anhydrous ethanol for ultrasonic dispersion for 90 minutes, with an ultrasonic frequency of 7.5kHz, removing anhydrous ethanol, and crushing to obtain an early strength prefabricated material a;

[0083] S4, adding silica sol and methyl orthosilicate to 1000g of anhydrous ethanol and stirring for 90min, adding 23% by mass ammonia solution thereto under stirring, adjusting the system to be neutral, continuing stirring for 90min, adding calcium formate and aluminum sulfate and stirring for 10min, standing for 7h, and vacuum drying to obtain early strength prefabricated material b;

[0084] S5. Evenly mix the composite water reducing agent, early strength prefabricated material a and early strength prefabricated material b, add the organosilicon defoaming agent and stir evenly, stir and dry at a temperature of 110°C at a stirring speed of 30r / min, cool to room temperature, and crush.

[0085] Comparative Example 2

[0086] A super high performance concrete early strength agent, whose raw materials include: 1200g of polypropylene, 150g of maleic anhydride grafted polypropylene, 250g of sodium chloride, 800g of polyethylene, 150g of sodium polyacrylate, 150g of aluminum chloride, 700g of diethanolamine, 300g of triisopropanolamine, 150g of sodium sulfate, 150g of calcium formate, 150g of aluminum sulfate, 1500g of composite water reducing agent, and 50g of silicone defoaming agent.

[0087] The composite water reducer is composed of polycarboxylic acid high-efficiency water reducer and sodium gluconate in a mass ratio of 9:1.

[0088] The preparation method of the ultra-high performance concrete early strength agent comprises the following steps:

[0089] S1, mixing polypropylene, maleic anhydride grafted polypropylene and sodium chloride uniformly, and melting them to obtain a molten material α;

[0090] S2, mixing polyethylene, sodium polyacrylate and aluminum chloride uniformly, and melting them to obtain a molten material β;

[0091] S3, using the molten material α as the core material and the molten material β as the skin material and feeding them into a composite spinning machine, spraying them out from a spinneret, cooling, cutting, soaking them in anhydrous ethanol and water in turn, ultrasonically washing them, vacuum drying, adding diethanolamine, triisopropanolamine, sodium sulfate, and 8000g of anhydrous ethanol for ultrasonic dispersion for 90 minutes, with an ultrasonic frequency of 7.5kHz, removing anhydrous ethanol, and crushing to obtain an early strength prefabricated material a;

[0092] S4, stirring calcium formate and aluminum sulfate for 10 minutes, standing for 7 hours, and vacuum drying to obtain early strength prefabricated material b;

[0093] S5. Evenly mix the composite water reducing agent, early strength prefabricated material a and early strength prefabricated material b, add the organosilicon defoaming agent and stir evenly, stir and dry at a temperature of 110°C at a stirring speed of 30r / min, cool to room temperature, and crush.

[0094] The early strength agent obtained by Example 5 and Comparative Examples 1-2 was added to concrete for comparative test. The concrete formula is as follows: 290kg of PO 42.5 silicate cement, 785kg of machine-made sand (0-4.75mm, fineness modulus of 2.8, stone powder content of 6.0%, mud block content of 0.2%, crushing index of 22%), 585kg of large stone (diameter>20mm, needle-like content (mass fraction) of 4%, crushing value of 18.2%, mud content of 0.8%), 418kg of small stone (diameter between 5-20mm, needle-like content (mass fraction) of 4%, crushing value of 18.2%, mud content of 0.8%), 70kg of Class II fly ash (water demand ratio of 101%, fineness of 21.7%, loss on ignition of 7.9%, activity of 74%), 2.26kg of early strength agent samples of each group, and 150kg of water.

[0095] Mix the raw materials of each group evenly according to the above proportions, and the mixing environment temperature is -8°C. Perform performance tests on the concrete obtained from each group according to GB / T8076-2008 "Concrete Admixtures".

[0096] like Figure 1-Figure 3 As shown, the early strength agent obtained in Example 5 can effectively help concrete have a higher air content in a low temperature environment, and has excellent slump and expansion. At the same time, it has a higher compressive strength (up to 30 MPa) at an early stage, and the later strength is guaranteed (up to 49 MPa or more).

[0097] Then, freeze-thaw tests were conducted on concrete blocks of each group that had been cured for 28 days, as follows:

[0098] The specimens were immersed in 20±2℃ water for 4 days, with the water level 25.0±5.0mm higher than the top surface of the specimens. After immersion, the specimens were taken out and the surface moisture was wiped off, and the appearance dimensions were measured and weighed. Each specimen was placed in a specimen box and then in a freeze-thaw chamber, with a 20mm gap between the specimen and the wall of the specimen box. In the quick freezing test, clean water should be injected into the specimen box, with the water level 50mm higher than the specimen. When the temperature in the freeze-thaw chamber drops to -18℃, the timing starts, and the freezing time in each freeze-thaw cycle is 4h. After freezing, water with a temperature of 19.0±1.0℃ is immediately added within 10min, with the water level more than 20mm higher than the specimen, and the thawing time is 4h. After thawing, the freeze-thaw cycle is considered to be over, and the next freeze-thaw cycle can be carried out.

[0099] After 100 freeze-thaw cycles, the freeze-thaw test was stopped, the compressive strength of the specimens was tested, and the strength loss rate was calculated. Figure 4 As shown, the early strength agent obtained in Example 5 can effectively improve the freeze-thaw resistance of concrete.

[0100] The applicant believes that this is because the present invention adopts polypropylene, maleic anhydride grafted polypropylene, and sodium chloride as the core layer raw materials, polyethylene, sodium polyacrylate, and aluminum chloride as the skin layer raw materials. Under the action of maleic anhydride grafted polypropylene, the bonding strength between the core layer and the skin layer is high. After ultrasonic washing with anhydrous ethanol and water, the aluminum chloride in the skin layer can be fully washed, and the formed through-hole structure can promote the further washing and escape of sodium chloride in the core layer, so that the obtained fiber structure not only has high adsorption strength for diethanolamine, triisopropanolamine, and calcium formate, but also provides expansion space for the sodium polyacrylate in the skin layer to absorb water and expand. At the same time, the pore structure in the core layer can keep the internal moisture constant, ensure the continuous hydration of cement, improve the microstructure of the hydration product, improve the compressive strength of the concrete, and then reduce the shrinkage rate and shorten the production cycle. With the precipitation of diethanolamine, triisopropanolamine, and sodium sulfate, the concrete can be made denser, and the impermeability and frost resistance of the concrete can be effectively improved.

[0101] Silica sol is compounded with tetraethyl orthosilicate, and calcium formate and aluminum sulfate are combined in the formed silica aerogel structure to form a dense three-dimensional network structure in the concrete. This not only promotes the bonding of internal particles, making the cementitious material denser, and the interfacial bonding stronger, but also further enhances the anti-seepage and anti-freeze-thaw effects. At the same time, because the new three-dimensional structure with nano-silica as the node is compounded on the basis of the original network structure of the concrete, it greatly reduces defects such as cracks, prolongs the service life and improves safety.

[0102] The present invention can accelerate the hydration effect, control the setting time of concrete, improve the early mechanical properties, enhance the impermeability and frost resistance, and improve the durability while increasing the water reduction effect.

[0103] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. An antifreeze type ultra-high performance concrete early strength agent, characterized in that: The raw materials include, by mass: 10-15 parts of polypropylene, 1-2 parts of maleic anhydride grafted polypropylene, 1-4 parts of sodium chloride, 5-10 parts of polyethylene, 1-2 parts of sodium polyacrylate, 1-2 parts of aluminum chloride, 4-10 parts of diethanolamine, 1-6 parts of triisopropanolamine, 1-2 parts of sodium sulfate, 1-2 parts of silica sol, 1-2 parts of methyl orthosilicate, 1-2 parts of calcium formate, 1-2 parts of aluminum sulfate, 10-20 parts of composite water reducer, and 0.1-1 parts of defoamer; Prepared by the following steps: S1, mixing polypropylene, maleic anhydride grafted polypropylene and sodium chloride uniformly, and melting them to obtain a molten material α; S2, mixing polyethylene, sodium polyacrylate and aluminum chloride uniformly, and melting them to obtain a molten material β; S3, using the molten material α as the core material and the molten material β as the skin material and feeding them into a composite spinning machine, spraying them out from a spinneret, cooling, cutting, soaking, ultrasonic washing, vacuum drying, adding diethanolamine, triisopropanolamine, sodium sulfate, and anhydrous ethanol for ultrasonic dispersion for 1-2 hours, removing the anhydrous ethanol, and crushing to obtain an early strength prefabricated material a ; S4. Add silica sol and methyl orthosilicate to anhydrous ethanol and stir for 1-2 hours. Add ammonia solution to the mixture under stirring to adjust the system to be neutral. Continue stirring for 1-2 hours. Add calcium formate and aluminum sulfate and stir for 5-15 minutes. Let stand for 5-10 hours and vacuum dry to obtain an early strength prefabricated material. b ; S5. Combine composite water reducing agent and early strength prefabricated material a , Early strength prefabricated materials b Mix evenly, add defoamer and stir evenly, stir and dry, cool to room temperature, and crush.

2. The antifreeze type ultra-high performance concrete early strength agent according to claim 1, characterized in that: Composite water reducers include: polycarboxylic acid high-efficiency water reducer and sodium gluconate.

3. The antifreeze type ultra-high performance concrete early strength agent according to claim 2, characterized in that: The mass ratio of polycarboxylic acid high-efficiency water reducer and sodium gluconate is 9-18:1-2.

4. The antifreeze type ultra-high performance concrete early strength agent according to claim 1, characterized in that: The defoaming agent is a silicone defoaming agent.

5. A method for preparing the antifreeze type ultra-high performance concrete early strength agent according to any one of claims 1 to 4, characterized in that: The steps include: S1, mixing polypropylene, maleic anhydride grafted polypropylene and sodium chloride uniformly, and melting them to obtain a molten material α; S2, mixing polyethylene, sodium polyacrylate and aluminum chloride uniformly, and melting them to obtain a molten material β; S3, using the molten material α as the core material and the molten material β as the skin material and feeding them into a composite spinning machine, spraying them out from a spinneret, cooling, cutting, soaking, ultrasonic washing, vacuum drying, adding diethanolamine, triisopropanolamine, sodium sulfate, and anhydrous ethanol for ultrasonic dispersion for 1-2 hours, removing the anhydrous ethanol, and crushing to obtain an early strength prefabricated material a ; S4. Add silica sol and methyl orthosilicate to anhydrous ethanol and stir for 1-2 hours. Add ammonia solution to the mixture under stirring to adjust the system to be neutral. Continue stirring for 1-2 hours. Add calcium formate and aluminum sulfate and stir for 5-15 minutes. Let stand for 5-10 hours and vacuum dry to obtain an early strength prefabricated material. b ; S5. Combine composite water reducing agent and early strength prefabricated material a , Early strength prefabricated materials b Mix evenly, add defoamer and stir evenly, stir and dry, cool to room temperature, and crush.

6. The method for preparing the antifreeze type ultra-high performance concrete early strength agent according to claim 5, characterized in that: In S3, after cutting, the pieces are immersed in anhydrous ethanol and water in sequence.

7. The method for preparing the antifreeze type ultra-high performance concrete early strength agent according to claim 5, characterized in that: In S3, the frequency of ultrasonic dispersion is 5-12 kHz.

8. The method for preparing the antifreeze type ultra-high performance concrete early strength agent according to claim 5, characterized in that: In S4, the mass fraction of the ammonia solution is 20-26%.

9. The method for preparing the antifreeze type ultra-high performance concrete early strength agent according to claim 5, characterized in that: In S5, the stirring and drying temperature is 100-120°C.

10. An application of the antifreeze type ultra-high performance concrete early strength agent according to any one of claims 1 to 4, characterized in that: The dosage of the antifreeze type ultra-high performance concrete early strength agent is 0.5-0.8% of the cementitious material in the concrete.